Scientific School “Interactive Methods of Management” - V. N. Knyazev (Управление)
The description of scientific school creation sources, scientific school development, main content of researches which were carried out during scientific school existence, development prospects of scientific school, involvement of teachers, researchers and graduate students have been presented in this paper.